Research on blow-out of shield tunnel in sandy soil with shallow burial - Shi, Yong-Xiang; Xi, Bao-Ping; Di, Qi-Guang; Wang, Feng-Nian (Frontiers in Earth Science, 2025)
Because of its non-viscosity, sand layer is easy to cause rock instability, which is always a difficult problem in tunnel excavation.This study employs an integrated approach of numerical simulation and theoretical analysis to investigate the phenomenon of shield tunnel faces blow-out in shallowly buried sandy soil strata. The research study the effects of burial depth to diameter ratio and the angle of internal friction on the ultimate support pressure and the shape of the failure zone. According to the simulation results, an analytical model for the blow-out of tunnel faces has been developed. The study reveals a linear relationship between the passive ultimate support pressure and the burial depth ratio, as well as the tangent of the friction angle. Upon tunnel passive failure, the failure zone is composed of a rigid core in the form of a lower wedge shape and an upper passive zone in the form of an inclined cylinder. Furthermore, using the wedge shape and inclined cylinder model and applying the theory of limit analysis, the corresponding formula for the ultimate support pressure has been derived. Compared to existing numerical models and classical analytical models, the analytical solution proposed in this paper is more accurate. The research on the failure zone found that an increase in the friction angle causes an enlargement of the failure zone and an increase in the dissipated power at the boundary, resulting in an exponential growth of the limit support pressure. The cohesion has a minimal effect on the shape and area of the failure zone, primarily manifesting as an increase in the dissipated power at the failure zone boundary. Additionally, the burial depth ratio has an insignificant effect on the lower failure zone, but as the cover ratio increases, the area of the upper failure zone gradually expands. At a smaller cover ratio, the weight of the soil plays a dominant role, whereas at a larger cover ratio, the effects of frictional force and cohesion at the failure zone boundary become more pronounced.